Digitalização e preservação digital: A experiência do Sistema Integrado de Bibliotecas da Universidade de São Paulo (SIBiUSP) - Pinto Ferreira, Sueli Mara Soares (2012)
The digitization and digital preservation activities are present in all the academic libraries actions today. This is done for the preservation of rare collections and special collections and also to ensure wide access to the intellectual production of the University. Here we have described the experiences developed by the University of Sao Paulo Integrated Library System (SIBiUSP) in reference to the systemic actions implemented, describing the technological infrastructure construction (hardware and software) and the institutional policies and standards for digitalization and digital preservation, presenting at the end the accomplishments with the content up to this date.